Influence of dietary calcium and phosphorus levels on growth performance, bone quality and apparent nutrient digestibility of broiler chickens - Abdulla, Nazim Rasul; Loh, Teck Chwen; Akit, Henny; Sazili, Awis Qurni; Foo, Hooi Ling (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The study investigated the effects of varying dietary calcium level on performance and digestibility of broiler chickens. A total of 126, 1-day old birds were fed with three dietary levels of calcium: phosphorus (NRC,1.25 and 1.5 NRC) for 6 weeks. Chicken fed diets containing 1.5 NRC requirements of Ca: P had lower body weight and apparent nutrient digestibility of organic matter, crude protein, ether extract and phosphorus compared with 1 and 1.25 NRC. In contrast, birds fed 1.25 NRC had significantly higher (p<0.05) bone quality, ash, Ca and P digestibility than NRC. It can be concluded that, increasing level of calcium: phosphorus up to 1.25 NRC requirement can improve broiler performance, bone quality and apparent nutrient digestibility.